DETERMINATION OF RATIONAL PARAMETERS OF SEPARATION OF MILLET SEEDS ON A GRAVITY IMPACT SEPARATOR (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
The article considers the issues of determining the rational parameters of cleaning a heap of millet seeds from separated seeds of weeds of mouse and chicken millet on a gravity multi-tiered impact separator. To determine the factors that have the greatest impact on the optimization criteria, an a priori ranking method was applied, and as a result, three main varying factors were identified, the levels of which were assigned based on the results of previous theoretical studies and design considerations. In the experiments, a three-level non-compositional Box-Benkin plan of the 2nd order is chosen.The regression equations were obtained, as a result of which two-dimensional cross-sections of the response surfaces of the optimization parameters were constructed. To ensure the interpretation of the obtained results of the study on the response surface, the method of two-dimensional sections is used. As a result of the graph-analytical analysis of the obtained expressions, the rational parameters of the value of the factors influencing the process of separating hard-to-separate weed seeds were determined.
Keywords: millet seeds; separation; process; gravity separator; rational parameters